Results of Experimental Research of the Corps That Provide Functionality to the Plantation Area of Poly Crops (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The article describes the results of experimental studies of the guiding plate casings used in the planting area of polys crops.